PENERAPAN STRATEGI SEPAK BOLA VERBAL DISERTAI LKS PADA PEMBELAJARAN BIOLOGI SISWA KELAS VIII MTsN PADANG SIBUSUK KABUPATEN SIJUNJUNG - NERITA S.Pd, M.Pd, SISKA (Jurnal Pelangi : Research of Education and Development, 2012)
This research has background of problem is low of students learningoutcome in Biologi Learning at MTSN Padang Sibusuk Kabupaten Sijunjung. It iscaused by some factors, such as passive students in learning, they didn’t havecooperation, and they often saw the book or asked to their friend when the testdone. Based on those problems, so the research would apply a strategy that calledverbal football. This research has purpose to know whether using verbal footballstrategy can improve students learning outcome in learning Biologi. Kinds of thisresearch is experimental research with research design is random control grouponly desigh. Population of this research are all of students at eight grade MTSNPadang Sibusuk Sijunjung. Technich of gathering sampling is purposivesampling, as experimental class is VIII2 and VIII1 as control class. Theinstrumentasi is final test of learning outcome and the data analysis is done byusing T-test. Base on analysis, taken means score of experimental class is 70,90,even though, control class is 60,18. From T-test analysis is taken tmt (2,88) > ttable(1,68). So it can be concluded that verbal football strategy by using students worksheet can improve learning outcome of Biology subject students of at eight gradeof MTSN Padang Sibusuk Kabupaten Sijunjung.